Translation simulation of a cylinder in a horizontal pipe. Issue 1 (1st January 2019) - Yao, Benchun; Ding, Qingxin; Zhang, Kang; Yang, Defu; Zhu, Xiaoxiao
Abstract : This article analyses the passive motion of a cylinder driven by flow in a horizontal pipe using the CFD method. In previous study by Yao et al. (2018) [A new openhole multistage hydraulic fracturing system and the ball plug motion in a horizontal pipe. Journal of Natural Gas Science and Engineering, Vol. 50, pp. 11–21], the motion of a cylinder in a horizontal pipe was investigated experimentally. The cylinder was observed contacting with the pipe bottom, meanwhile it behaved like a guided body with its axis parallel to that of the horizontal pipe. Apart from some observations, it was very hard to gain more knowledge about the flow distribution around the cylinder and the role played by the cylinder's eccentricity in the translation. In order to conduct an extended research, this article concentrates on a general model which considers eccentricity and cylinder–pipe interaction. Moreover, a novel yet efficient approach, which investigates the translation process in a control volume attached to the cylinder, is proposed to simulate the motion utilizing the moving reference frame technique. A series of numerical simulations, with various cylinder dimensions and eccentricities, are conducted to investigate the dynamics of the cylinder and fluid. Meanwhile, the validity of the simulations is proved by comparing the results of experiments with the simulations. Lastly, an error analysis is conducted, and the limitations of this study are highlighted.